Chapter 8 Mixed Reality for Industry 4.0 in Manufacturing Systems - Kolla, Sri (Taylor & Francis, 2024)
A revolutionary computer-generated environment called Mixed Reality (MR) combines the real and virtual worlds. The MR environment can be created using two rapidly developing technologies: Augmented Reality (AR) and Virtual Reality (VR), with varying degrees of awareness of reality. With the introduction of Industry 4.0 (I4.0) in the manufacturing systems, AR & VR technologies have seen adoption in various stages of the product life cycle. AR can improve the manufacturing tasks such as quality inspection, assembly instructions, maintenance, & safety by enhancing reality with virtual aides. On the other hand, VR can be a beneficial technology for training activities. This chapter mainly focuses on different AR systems and their interaction modalities. Moreover, the chapter also covers system architectures for two different AR systems (Hand-Held Devices & Head Mounted Devices) and validates the architectures with relevant case studies. Finally, a brief description of the VR technology is presented with a relevant case study.